Social and Communication Skills Predict Imitation Abilities in Children with Autism - So, Wing-Chee; Wong, Miranda Kit-Yi; Lam, Ka-Yee (Frontiers in Education, 2016)
This study examined whether social and communicative skills would predict the ability to imitate conventional-interactive gestures (e.g., HAND WAVING for saying goodbye) in children with autism spectrum disorders (ASD). Twenty 6- to 11-year-old Chinese-speaking children with ASD participated. Their social and communicative skills were assessed based on their caregivers’ ratings on their social and communication impairments and the observation of their gesture production in spontaneous interactions with the caregivers three months prior to the administration of the gesture imitation task. After controlling for gesture recognition and visual-motor coordination skills, the results of the partial correlation analyses have shown that there was significant association among the number of conventional-interactive gestures imitated accurately, the caregivers’ ratings, and the number of conventional-interactive gestures produced during interactions. Four regression analyses were thus conducted. We found the severity of social and communication impairments predicted the imitation of communicative gestures, with such relation mediated by the production of conventional-interactive gestures during the interactions. Overall, the results suggest that social and communication skills may play a causal role in imitation abilities in children with autism.